The Mapping Spatial Family Research: A Semi-Automated Computational Review - Mlýnek, Pavel (European Journal of Geography, 2026)
Family structures have undergone significant transformations, evolving from traditional nuclear models to more diverse and fragmented forms. While these shifts – driven by demographic changes, technological advancements, and evolving social norms – are fundamentally anchored in space, a "Geography of Family" remains methodologically dispersed and on the margins of mainstream research. This study employs a semi-automated computational mapping review, utilising ASReview and VOSviewer, to categorise how space is currently operationalised in explicitly spatial family-oriented research. The analysis identifies three primary conceptual clusters: space as a static context for social ties, space as a dynamic process of mobility, and space as a structural determinant of distance friction. Crucially, the review revealed that while micro-level family dynamics and macro-level structural conditions are well-documented, they are rarely simultaneously integrated into the same analytical models alongside active spatial metrics. Based on the mapped evidence, the study proposes a functional "triadic model" anchored in time, recommending a framework that systematically integrates micro-level ties, macro-level structures, and spatial dynamics. This approach enables the discipline to move beyond descriptive regional mappings towards robust causal explanations, advocating for the broader adoption of spatial tools such as Geographic Information Systems (GIS) to better understand kinship networks and intergenerational resilience in a changing world. Highlights: Analysis identifies three clusters: Space as Context, Process, and Structure. Fragmented infrastructures and methodological nationalism constrain the field. Integrating spatial analysis tools can unlock causal explanations for family change.